Study of intranasal midazolam versus intranasal ketamine as a premedication in children undergoing surgical procedures - Marathe, Himanshu; Chhajwani, Sunil (International Journal of Research in Medical Sciences, 2019)
Background: Usage of premedication in children undergoing surgery is almost imperative and various medications have been used with varying success. The present study was aimed at comparison of intranasal midazolam and intranasal ketamine as a premedication in children by assessing acceptability of the drug by patients, ease at parent separation, level of sedation at the time of induction and facilitation of intravenous cannulation. Methods: In this comparative observational study, 60 eligible participants were randomly divided into two groups of 30 each on the basis of preanaesthetic medication received: those intranasal midazolam group and intranasal ketamine group. At 30 minutes after intranasal dose, sedation, separation from parents and intravenous cannula acceptance was evaluated on four point score scale. Children were constantly observed for occurrence of possible adverse effects and the same were duly noted. Results: The two groups were similar with respect to age, gender and body weight distribution. Twenty four patients (80%) in both ketamine and midazolam groups were observed to become drowsy, while 6 patients (20%) in ketamine group were asleep, compared to 0 patients in midazolam group (p=0.024). Thirteen (43.3%) patients from midazolam group had poor parenteral separation, as compared to 0 patients from ketamine group. And Comparison of intravenous cannula acceptance revealed the acceptance to be good in 26 (86.7%) patients in ketamine group as compared to 10 (33.3%) patients in midazolam group (p<0.001). Conclusions: Ketamine when given in a dose of 5 mg/kg via intranasal route is better than midazolam given in a dose of 0.2mg/kg intranasally, as a premedication in children.